Electronic, optical and thermoelectric properties of WSe2–InN 2D interface: A DFT study. (1st October 2022) - Ghadri, Asghar; Boochani, Arash; Hojabri, Alireza; Hajakbari, Fatemeh
Abstract: Based on the density functional theory, mechanical stability, structural, electronic, optical, thermoelectric, and band alignment properties, WSe2 –InN graphene has been investigated at three different distances. The calculations are based on GGA approximations and van der Waals switch in three distances d1 = 4.1528A o, d2 = 4.4402A o, d3 = 5.6048A o between WSe2 and InN layers, which we saw the equilibrium volume, but at distance d2 we observed the most stability conditions. Electronic studies show that this interface has 0.49eV indirect energy gap. The optical properties with BSE approximation are most consistent with its electronic properties and the highest optical response occurred in the UV region. The optical gap in the imaginary part of the dielectric function is entirely consistent with the electronic gap. The merit coefficient of this interface at low temperatures is close to one. Also, power factor calculations show that this case is a suitable option for power generator applications. Highlights: WSe 2 –InN 2D interface has semiconductor property. WSe 2 –InN 2D interface has the 3eV optical gap. WSe 2 –InN 2D interface has high ZT at 50K.